The Role of Agricultural Cooperatives in Prospering Farming Communities - Sugiarto, Apprillia Anggraeni; Dinaloni, Diah; Sudarwati, Ninik; Amri, Fahimul (Politeknik Negeri Jember, 2025)
The Sarana Agro Lestari Agricultural Cooperative in Jombang Regency, East Java, addresses the issue of low farmer income caused by limited access to capital, market price fluctuations, and restricted access to technology and broader markets. This study aims to analyze the cooperative's role in improving farmers' welfare through empowerment programs. A qualitative approach was employed, gathering data through in-depth interviews with cooperative managers and farmer group representatives, as well as analyzing supporting documents. The results show that the cooperative provides benefits such as financial access, affordable production inputs, modern technology training, and more effective crop marketing. However, challenges like insufficient capital, limited facilities, and price fluctuations hinder the cooperative's optimal role. Strengthening partnerships, product diversification, and technological innovation are recommended to enhance the cooperative's sustainability in supporting farmers' welfare.